The Grønnedal-Íka alkaline complex, South Greenland. The structure and geological history of the complex - Emeleus, C.H. (Meddelelser om Grønland, 1964)
The Grønnedal-Íka alkaline complex consists of predominantly foyaitic nepheline syenites and carbonatite intruding gneisses and metasediments near Ivigtut, South Greenland. The complex is intruded by numerous dolerite, basalt, trachyte and phonolite dykes; it is severely faulted. The complex is considered to be of Precambrian age. Several distinct intrusive phases are recognised in the syenites: an early Lower Series, mainly of medium-grained well-laminated foyaite, is overlain by a raft-like mass of gneiss that separates it from a later, Upper Series containing foyaite, a pyroxene-rich syenite, and pulaskite in small amounts. The Upper Series rocks are generally well-laminated and in addition a small amount of conformable mafic layering is developed in the pyroxene-rich member. There are structural and textural similarities between the laminated and layered members of the Lower and Upper Series, and igneous cumulates. The north-western margin of the complex is defined by a curving dyke-like intrusion of granular syenite, considered to be an incomplete ringdyke. The Upper Series syenites are cut by a steep-sided body of porphyritic xenolithic syenite, the latest major syenite intrusion in the complex. The nepheline syenites have been intruded by carbonatite which was forcibly emplaced with brecciation and metasomatic alteration of its surroundings. The carbonatite is calcite-rich (Soivite) with variable quantities of siderite, sphalerite, apatite and other minerals. The earliest dykes cutting the alkaline complex are a sparse set of lamprophyres, these were followed by thin sheets and dykes of dolerite containing numerous plagioclase phenocrysts, often several centimetres in length. There then followed several thick dykes of olivine dolerite, striking between E.-W. and N.E.-S.W. and members of a regional swarm. These are cut by a group of thin, microporphyritic basalts and subsequently by two groups of trachytic and phonolitic dykes; an early sparse set striking approximately N.N.W.-S.S.E. and restricted to the vicinity of the complex, and a later, E.N.E.-W.S.W. striking set that are part of an extensive swarm in the country around Ivigtut. Finally, faulting took place in three stages: i) an early group of dextral transcurrent faults striking about N. 10-30 E., ii) an E.S.E.-W.N.W. striking sinistral transcurrent fault, the Laksenæs Fault, and iii) a late dextral transcurrent group striking approximately N.-S. There is evidence of some overlap between the emplacement of the trachytic and phonolitic dykes, and the faulting. The present outline of the complex measures approximately 8 km. from N.N.W. to S.S.E. and 2.8 km. from E.N.E. to W.S.W. When allowance is made for the distortion due to dyke intrusion and faulting the original outline is found to have been about 6 km. from N.W. to S.E. and 3.5 from N.E. to S.W. The original structure is seen to have been relatively simple, consisting of two series of laminated and layered syenites with centrally-directed structures separated by a raft of gneiss, and a later central stock of porphyritic xenolithic syenite. The syenites were cut by a central plug of xenolithic carbonatite, zoned from calcite-rich margins to a core containing appreciable quantities of siderite and other minerals. Metamorphism of the sideriterich core by an olivine dolerite dyke resulted in the formation of a small body of magnetite-rich carbonate rock in the centre of the complex.